Overexpression of nerve growth factor in epidermis of transgenic mice causes hypertrophy of the peripheral nervous system - Albers, KM (J Neurosci, 1994)
Survival of developing neurons is dependent on access to a limited supply of target-derived neurotrophic factors. NGF is the most extensively characterized of these molecules and during development is synthesized by neuronal and nonneuronal target tissues such as the skin. To investigate how target-derived NGF affects neuron survival and development of the PNS, we used an epidermal-specific gene promoter to produce transgenic mice that overexpress the mouse NGF cDNA in skin. Analysis of transgenic skin mRNA synthesis by Northern and in situ hybridizations showed increased levels of transgene-derived mRNA in the epidermis and associated hair follicles. The increase in NGF mRNA correlated with a hypertrophy of peripheral sensory and sympathetic nerves. Immunological analysis of skin using an anti-150 kDa neurofilament antibody showed numerous large nerve bundles and fibers coursing throughout the dermis. Increased numbers of nerve processes in the transgenic skin had immunoreactivity for calcitonin gene-related peptide and tyrosine hydroxylase, indicating that both the sensory and sympathetic systems were hypertrophied. The trigeminal and superior cervical ganglia were greatly enlarged. Cell counts of trigeminal ganglia of control and transgenic mice showed a 26–117% increase in the number of neurons in the transgenics, indicating a reduction or total prevention of the program of naturally occurring cell death. These results demonstrate that NGF production by the epidermal target tissue controls neuronal survival, and in so doing, establishes the level of innervation.